2022
DOI: 10.20892/j.issn.2095-3941.2022.0469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management and survival outcomes of patients with different molecular subtypes of diffuse gliomas in China (2011–2017): a multicenter retrospective study from CGGA

Abstract: Objective: We aimed to summarize the clinicopathological characteristics and prognostic features of various molecular subtypes of diffuse gliomas (DGs) in the Chinese population. Methods: In total, 1,418 patients diagnosed with DG between 2011 and 2017 were classified into 5 molecular subtypes according to the 2016 WHO classification of central nervous system tumors. The IDH mutation status was determined by immunohistochemistry and/or DNA sequencing, and 1p/19q codeletion was detected with fluorescence in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…The treatment regimen remained lack of evidences under new classi cation of IDH-mutant astrocytoma, WHO grade 4. A multi-center study shown that patients with primary IDH-mutant glioblastoma can have an overall survival bene t from TMZ and concurrent radiochemotherapy [12]. Followed the progression of WHO 4 glioblastoma/astrocytoma, the recurrent IDH-mutant astrocytoma was less likely to extend beyond gross tumor volume and indicated a modi ed plan of radiotherapy or radiochemotherapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment regimen remained lack of evidences under new classi cation of IDH-mutant astrocytoma, WHO grade 4. A multi-center study shown that patients with primary IDH-mutant glioblastoma can have an overall survival bene t from TMZ and concurrent radiochemotherapy [12]. Followed the progression of WHO 4 glioblastoma/astrocytoma, the recurrent IDH-mutant astrocytoma was less likely to extend beyond gross tumor volume and indicated a modi ed plan of radiotherapy or radiochemotherapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have associated the molecular features of glioma with clinical classification. Patients with glioma without IDH mutant or 1p/19q co‐deleted had worse outcomes 62–64 . In addition, tumors with different IDH and 1p/19q status undergo distinct cell‐state changes at recurrence, which may interfere with the comparison of the microenvironment between primary gliomas and recurrent gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…[47] The Chinese Glioma Genome Atlas (CGGA) cohort (n = 693 tumors) processed RNAseq was downloaded from http://cgga.org.cn/. [102][103][104][105] Statistical Analysis: All data points were plotted and analyzed. N > 3 for all experiments, and are specifically stated in figure legends.…”
Section: Methodsmentioning
confidence: 99%